FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL STRESS MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS TANJUNGPURA - Tri Wahyu Rizcay; Okianna Okianna; M Basri (Universitas Tanjungpura, 2022)
This study aims to determine the factors that influence the financial stress of Economic Education students at Tanjungpura University. The indicators studied included parents' income, financial literacy, gender and place of residence. This study uses a qualitative approach in the form of a case study. The data collection technique was done by interviews and documentation. The object of this study is the student of the Regular Economics Education study program in the 2016-2017 class of Tanjungpura University.Data retrieval in the PreResearch using google form to find out in advance whether Regular Economics Education students have experienced financial stress and financial difficulties and the results show that 109 Regular Economics Education students have experienced financial stress and financial difficulties and 76 Regular Economics Education students have never experienced financial stress and financial difficulties. This study used interview and documentation techniques and interview techniques were conducted in a structured manner using interview guidelines. The results of this study indicate that there are three factors that have a relevant influence, namely, financial literacy, gender and place of residence, while one factor that does not have a relevant influence is parents' income on the financial stress of Economic Education students at Tanjungpura University.Keywords: Financial stress, parents’income, financial literacy, gender and place of residence.